Ecosystems as unit operations for local techno‐ecological synergy: Integrated process design with treatment wetlands. Issue 7 (3rd February 2018) - Gopalakrishnan, Varsha; Bakshi, Bhavik R.
Abstract : Despite the critical importance of ecological systems for sustaining all chemical and manufacturing processes, process design has kept nature outside its system boundary. Recent efforts for sustainable process design aim to reduce environmental impact, but no design method considers the capacity of ecosystems to supply the goods and services that are needed to sustain a process. Overcoming this deficiency of conventional process design is essential to transform the chemical industry into an activity that respects ecological constraints and results in a net positive societal impact. As an important step toward meeting this goal, this work expands the boundary of process design to include ecosystems as unit operations in traditional design. Similar to tasks performed by conventional unit operations, ecological processes perform ecosystem functions resulting in goods and services required by the technological system. The goal behind designing integrated techno‐ecological process flowsheets is to balance the ecosystem service demand of technological systems with the ecosystem service supply of ecological systems. Systems are optimized to balance the demand and supply subject to unit operation level constraints of technological and ecological systems, and interactions between detailed process level variables and ecological variables are explored. The Techno‐Ecological Synergy (TES) Design method is developed and applied to a biofuel production system, considering ecosystem services like water provisioning and water quality regulation provided by wetland ecosystems. Comparing the integrated TES design with conventional techno‐centric design shows that TES design can result in net positive impact manufacturing: a case where the ecosystem service supply is equal to or exceeds the demand, with little or no compromises in process profitability. These results should encourage close integration between technological and ecological systems while designing sustainable processes, and identify many challenges for developing TES of individual processes and across the life cycle. © 2018 American Institute of Chemical Engineers AIChE J, 64: 2390–2407, 2018